Effect of melatonin implantation prior to ovsynch plus cidr protocol on subsequent ovarian activity and pregnancy rate in summer anestrous Murrah buffaloes - Ghuman, Sarvpreet Singh; Honparkhe, Mrigank; Singh, Bilawal (Buffalo Bulletin, 2023)
For assessing the impact of melatonin pre-treatment in summer anestrous Murrah buffaloes on subsequent reproductive activity of a fixed time artificial insemination (FTAI) protocol, 83 anestrous Murrah buffaloes were subcutaneously inserted 2x4 mm size absorbable melatonin (MT) implants (18 mg/50 kg b wt) at the base of left ear and 38 Murrah buffaloes were used as non-implanted controls. On day 35 post-MT, the Treatment and Control group Murrah buffaloes were subjected to FTAI protocol (Ovsynch plus CIDR). Ovarian ultrasonography and jugular vein blood sampling was carried out on day 7 and 10 of protocol and on day 7-post AI. Overall pregnancy rate on day 90 post-AI in MT group was higher compared to Control group (55.4 vs 31.6%, P<0.05), along with the higher (P>0.05) plasma progesterone on day 7 of FTAI protocol in Murrah buffaloes of the former group which conceived subsequently compared to their non-pregnant counterparts. Moreover, MT group had higher (P>0.05) increase in dominant follicle diameter between day 7 and 10 of protocol compared to Control group. On day 7 post-AI, the luteal profile in pregnant Murrah buffaloes of MT group was better (P<0.05) compared to their counterparts in Control group (CL: 14.80±0.70 vs 10.82±0.46 mm, P4: 1.54±0.07 vs 1.04±0.08 ng/ml). In conclusion, melatonin pre-treatment in summer anestrous Murrah buffaloes could be associated with better luteal activity and higher pregnancy rate in the Ovsynch+CIDR protocol.